Biome-scale spatial patterns of avian abundance reveal proactive conservation opportunities in North American grasslands - Caleb P. Roberts; Victoria M. Donovan; Samantha M. Cady; Brandon P.M. Edwards; Scott Morford; David Naugle; Rheinhardt Scholtz; Dirac Twidwell; Daniel R. Uden; Dillon Fogarty (Biological Conservation, 2026)

Impact of 10 years of adaptive multi-paddock grazing on soil carbon and beef's greenhouse gas footprint in the US Upper Midwest - Lautaro Garcia; Paige L. Stanley; Joao P. Sacramento; Jasmine A. Dillon; Mariko Thorbecke; Logan R. Thompson; Vrinda Ambike; Prateek Sharma; Sutie Xu; Marilia B. Chiavegato; Matt R. Raven; Bruno Basso; et al. (Agricultural Systems, 2026)

Damage equivalent strain as a metric for tidal turbine blade fatigue scenario comparison - J. Dillenburger-Keenan; C. Courade; C. Dillon; H. Knoblauch; P. Cronin; C. Frost (Ocean Engineering, 2026)

Expand or better manage protected areas: A framework for minimizing extinction risk when threats are concentrated near edges - Brendan G. Dillon; Hugh P. Possingham; Matthew H. Holden (Biological Conservation, 2025)

High-intensity fire supports restoration of grassland species richness and community composition following woody encroachment - Victoria M. Donovan; Alison K. Ludwig; Dillon T. Fogarty; Caleb P. Roberts; Dirac Twidwell (Journal of Environmental Management, 2025)

Optimising parent selection in plant breeding: comparing metaheuristic algorithms for genotype building - S. Yadav; S. Dillon; M. McNeil; E. Dinglasan; R. Mago; P. Dodds; L. Hickey; B. J. Hayes (Theoretical and Applied Genetics, 2025)
Stacking desirable haplotypes across the genome to develop superior genotypes has been implemented in several crop species. A major challenge in Optimal Haplotype Selection is identifying a set of parents that collectively contain all desirable haplotypes, a complex combinatorial problem with countless possibilities. In this study, we evaluated the performance of metaheuristic search algorithms (MSAs)—genetic algorithm (GA), differential evolution (DE), particle swarm optimisation (PSO), and simulated annealing (SA) for optimising parent selection under two genotype building (GB) objectives: Optimal Haplotype Selection (OHS) and Optimal Population Value (OPV). Using a diverse wheat population of 583 lines genotyped for 29,972 SNPs, forming 7645 haplotype blocks and phenotyped for stripe rust scores, we assessed each algorithm’s performance across fitness optimisation, convergence speed, and computational efficiency. GA consistently achieved high fitness and rapid convergence, while DE showed robustness but required longer runtime and careful tuning. PSO performed well under the OHS criterion but was less effective for OPV. SA, although computationally lighter, was less consistent in finding optimal solutions. Simulation over 100 breeding cycles showed that OHS outperformed both OPV and GEBV-based selection in long-term genetic gain and diversity retention. OHS maintained heterozygosity and additive variance, which are key for sustainable improvement, while GEBV selection led to early allele fixation. Our findings underscore the potential of GB strategies that prioritise the collective performance of parent sets rather than individual ranking to enhance selection outcomes in genomic-assisted breeding programmes.

Population increases of the threatened American burying beetle (Nicrophorus americanus) linked to large-scale collaborations in a working lands ecoregion - Caleb P. Roberts; Alison K. Ludwig; Dillon T. Fogarty; Erica F. Stuber; Daniel R. Uden; Thomas L. Walker; Dirac Twidwell (Biological Conservation, 2025)

Organic acid preservation of cereal grains improves grain quality, growth performance, and intestinal health of post-weaned pigs - Shane Maher; Torres Sweeney; Dillon P. Kiernan; Marion T. Ryan; Vivian Gath; Stafford Vigors; Kathryn Ruth Connolly; John V. O’Doherty (Animal Feed Science and Technology, 2024)

Effects of ocean acidification on the interaction between calcifying oysters (Ostrea chilensis) and bioeroding sponges (Cliona sp.) - Imke M. Böök; Erik C. Krieger; Nicole E. Phillips; Keith P. Michael; James J. Bell; Wayne D. N. Dillon; Christopher E. Cornwall (Frontiers in Marine Science, 2024)
Ocean acidification can negatively affect a broad range of physiological processes in marine shelled molluscs. Marine bioeroding organisms could, in contrast, benefit from ocean acidification due to reduced energetic costs of bioerosion. Ocean acidification could thus exacerbate negative effects (e.g. reduced growth) of ocean acidification and shell borers on oysters. The aim of this study was to assess the impact of ocean acidification on the oyster Ostrea chilensis , the boring sponge Cliona sp., and their host-parasite relationship. We exposed three sets of organisms 1) O. chilensis , 2) Cliona sp., and 3) O. chilensis infested with Cliona sp. to pH T 8.03, 7.83, and 7.63. Reduced pH had no significant effect on calcification, respiration and clearance rate of uninfested O. chilensis . Low pH significantly reduced calcification leading to net dissolution of oyster shells at pH T 7.63 in sponge infested oysters. Net dissolution was likely caused by increased bioerosion by Cliona sp. at pH T 7.63. Additionally, declining pH and sponge infestation had a significant negative antagonistic effect (less negative than predicted additively) on clearance rate. This interaction suggests that sponge infested oysters increase clearance rates to cope with higher energy demand of increased shell repair resulting from higher boring activity of Cliona sp. at low seawater pH. O. chilensis body condition was unaffected by sponge infestation, pH, and the interaction of the two. The reduction in calcification rate suggests sponge infestation and ocean acidification together would exacerbate direct (reduced growth) and indirect (e.g., increased predation) negative effects on oyster health and survival. Our results indicate that ocean acidification by the end of the century could have severe consequences for marine molluscs with boring organisms.

Nitrate leaching on Irish grassland dairy farms: A review - D.J. Murphy; P. Dillon; M. O’ Donovan; L. Shalloo; E. Ruelle (European Journal of Agronomy, 2024)

Metabolomes of bumble bees reared in common garden conditions suggest constitutive differences in energy and toxin metabolism across populations - Ellen C. Keaveny; Mitchell R. Helling; Franco Basile; James P. Strange; Jeffrey D. Lozier; Michael E. Dillon (Journal of Insect Physiology, 2023)

Skin and eye irritancy assessment of six lactic acid bacteria strains - Ivana Nikodinoska; Christina Spohr; Gerald P. Dillon; Colm A. Moran (Regulatory Toxicology and Pharmacology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Body mass and sex, not local climate, drive differences in chill coma recovery times in common garden reared bumble bees - K. Jeannet Oyen; Laura E. Jardine; Zachary M. Parsons; James D. Herndon; James P. Strange; Jeffrey D. Lozier; Michael E. Dillon (Journal of Comparative Physiology B, 2021)

The Currency of Conservation: How Is Landscape Extent Applied in Conservation Planning? - Kirsten Solmundson; Jeff Bowman; Elizabeth Adey; Jennifer E. Baici; Rachel M. Dillon; Arthur E. Dupuis; Robby R. Marrotte; Samantha J. Morin; Sasha L. Newar; Paul P. O’Brien; Laura M. Scott (Current Landscape Ecology Reports, 2020)

Local adaptation across a complex bioclimatic landscape in two montane bumble bee species - Jason M. Jackson; Meaghan L. Pimsler; Kennan J. Oyen; James P. Strange; Michael E. Dillon; Jeffrey D. Lozier (Molecular Ecology, 2020)
Understanding evolutionary responses to variation in temperature and precipitation across species ranges is of fundamental interest given ongoing climate change. The importance of temperature and precipitation for multiple aspects of bumble bee ( Bombus ) biology, combined with large geographic ranges that expose populations to diverse environmental pressures, make these insects well‐suited for studying local adaptation. Here, we analyzed genome‐wide sequence data from two widespread bumble bees, Bombus vosnesenskii and Bombus vancouverensis , using multiple environmental association analysis methods to investigate climate adaptation across latitude and altitude. The strongest signatures of selection were observed in B. vancouverensis , but despite unique responses between species for most loci, we detected several shared responses. Genes relating to neural and neuromuscular function and ion transport were especially evident with respect to temperature variables, while genes relating to cuticle formation, tracheal and respiratory system development, and homeostasis were associated with precipitation variables. Our data thus suggest that adaptive responses for tolerating abiotic variation are likely to be complex, but that several parallels among species can emerge even for these complex traits and landscapes. Results provide the framework for future work into mechanisms of thermal and desiccation tolerance in bumble bees and a set of genomic targets that might be monitored for future conservation efforts.

Effects of chronic pain history on perceptual and cognitive inhibition - Mark Hollins; Chloe P. Bryen; Dillon Taylor (Experimental Brain Research, 2020)

Hydrologic and cost benefit analysis at local scale of streambed recharge structures in Rajasthan (India) and their value for securing irrigation water supplies - Y. Dashora; P. Dillon; B. Maheshwari; P. Soni; H. K. Mittal; R. Dashora; P. K. Singh; R. C. Purohit; P. Katara (Hydrogeology Journal, 2019)

Sixty years of global progress in managed aquifer recharge - P. Dillon; P. Stuyfzand; T. Grischek; M. Lluria; R. D. G. Pyne; R. C. Jain; J. Bear; J. Schwarz; W. Wang; E. Fernandez; C. Stefan; M. Pettenati; et al. (Hydrogeology Journal, 2019)

Distance, elevation and environment as drivers of diversity and divergence in bumble bees across latitude and altitude - Jason M. Jackson; Meaghan L. Pimsler; Kennan Jeannet Oyen; Jonathan B. Koch‐Uhuad; James D. Herndon; James P. Strange; Michael E. Dillon; Jeffrey D. Lozier (Molecular Ecology, 2018)
Identifying drivers of dispersal limitation and genetic differentiation is a key goal in biogeography. We examine patterns of population connectivity and genetic diversity using restriction site‐associated DNA sequencing ( RAD seq) in two bumble bee species, Bombus vosnesenskii and Bombus bifarius, across latitude and altitude in mountain ranges from California, Oregon and Washington, U.S.A. Bombus vosnesenskii , which occurs across a broader elevational range at most latitudes, exhibits little population structure while B. bifarius , which occupies a relatively narrow higher elevation niche across most latitudes, exhibits much stronger population differentiation, although gene flow in both species is best explained by isolation with environmental niche resistance. A relationship between elevational habitat breadth and genetic diversity is also apparent, with B. vosnesenskii exhibiting relatively consistent levels of genetic diversity across its range, while B. bifarius has reduced genetic diversity at low latitudes, where it is restricted to high‐elevation habitat. The results of this study highlight the importance of the intersect between elevational range and habitat suitability in influencing population connectivity and suggest that future climate warming will have a fragmenting effect even on populations that are presently well connected, as they track their thermal niches upward in montane systems.

Managing aquifer recharge and sustaining groundwater use: developing a capacity building program for creating local groundwater champions - Y. Jadeja; B. Maheshwari; R. Packham; Hakimuddin Bohra; R. Purohit; B. Thaker; P. Dillon; S. Oza; S. Dave; P. Soni; Y. Dashora; R. Dashora; et al. (Sustainable Water Resources Management, 2018)

A simple method using farmers’ measurements applied to estimate check dam recharge in Rajasthan, India - Y. Dashora; P. Dillon; B. Maheshwari; P. Soni; R. Dashora; S. Davande; R. C. Purohit; H. K. Mittal (Sustainable Water Resources Management, 2018)

Pre-operative Screening and Manual Drilling Strategies to Reduce the Risk of Thermal Injury During Minimally Invasive Cochlear Implantation Surgery - Neal P. Dillon; Loris Fichera; Kyle Kesler; M. Geraldine Zuniga; Jason E. Mitchell; Robert J. Webster; Robert F. Labadie (Annals of Biomedical Engineering, 2017)

c-Fos induction by gut hormones and extracellular ATP in osteoblastic-like cell lines - Elda Leonor Pacheco-Pantoja; Jane P. Dillon; Peter J. M. Wilson; William D. Fraser; James A. Gallagher (Purinergic Signalling, 2016)

Stormwater Quality Review to Evaluate Treatment for Drinking Water Supply via Managed Aquifer Recharge - D. Page; J. Vanderzalm; P. Dillon; D. Gonzalez; K. Barry (Water, Air, & Soil Pollution, 2016)

Cellulase and Xylanase Expression in Response to Different pH Levels of Penicillium echinulatum S1M29 Medium - Laísa dos Reis; Willian Daniel Hahn Schneider; Roselei Claudete Fontana; Marli Camassola; Aldo J. P. Dillon (BioEnergy Research, 2014)

Relationships between body size and trophic position of consumers in temperate freshwater lakes - A. D. Persaud; P. J. Dillon; L. A. Molot; K. E. Hargan (Aquatic Sciences, 2012)

Mitochondrial respiration and succinate dehydrogenase are suppressed early during entrance into a hibernation bout, but membrane remodeling is only transient - Dillon Chung; Graham P. Lloyd; Raymond H. Thomas; Chrisopher G. Guglielmo; James F. Staples (Journal of Comparative Physiology B, 2011)

Incubating Rainbow Trout in Soft Water Increased Their Later Sensitivity to Cadmium and Zinc - Christopher A. Mebane; Daniel P. Hennessy; Frank S. Dillon (Water, Air, & Soil Pollution, 2010)

Natural lake level fluctuation and associated concordance with water quality and aquatic communities within small lakes of the Laurentian Great Lakes region - M. S. White; M. A. Xenopoulos; K. Hogsden; R. A. Metcalfe; P. J. Dillon (Hydrobiologia, 2008)

Glasgow Lake: an early-warning sentinel of lake acidification in Cape Breton Highlands National Park (Nova Scotia, Canada) - Alexandra M. Gerber; Brian K. Ginn; Colin J. Whitfield; Peter J. Dillon; Brian F. Cumming; John P. Smol (Hydrobiologia, 2008)

Decolorization of textile dyes by enzymatic extract and submerged cultures of Pleurotus sajor-caju - Fernanda M. Munari; Tamara A. Gaio; Raquel Calloni; Aldo J. P. Dillon (World Journal of Microbiology and Biotechnology, 2008)

Nitrogen Stable Isotopes of Macrophytes Assess Stormwater Nitrogen Inputs to an Urbanized Estuary - Kevin S. Dillon; Jeffrey P. Chanton (Estuaries and Coasts, 2008)

Developing Acute-to-chronic Toxicity Ratios for Lead, Cadmium, and Zinc using Rainbow Trout, a Mayfly, and a Midge - Christopher A. Mebane; Daniel P. Hennessy; Frank S. Dillon (Water, Air, & Soil Pollution, 2008)

Delayed response of diatom assemblages to sewage inputs in an Arctic lake - Neal Michelutti; Mark H. Hermanson; John P. Smol; Peter J. Dillon; Marianne S. V. Douglas (Aquatic Sciences, 2007)

Chemically inducible expression of the PHB biosynthetic pathway in Arabidopsis - Lauralynn Kourtz; Kevin Dillon; Sean Daughtry; Oliver P. Peoples; Kristi D. Snell (Transgenic Research, 2007)

Sorghum resolved as a distinct genus based on combined ITS1, ndhF and Adh1 analyses - S. L. Dillon; P. K. Lawrence; R. J. Henry; H. J. Price (Plant Systematics and Evolution, 2007)

Pharmacology of P2X channels - Joel R. Gever; Debra A. Cockayne; Michael P. Dillon; Geoffrey Burnstock; Anthony P. D. W. Ford (Pflügers Archiv - European Journal of Physiology, 2006)

Sorghum laxiflorum and S. macrospermum, the Australian native species most closely related to the cultivated S. bicolor based on ITS1 and ndhF sequence analysis of 25 Sorghum species - S. L. Dillon; P. K. Lawrence; R. J. Henry; L. Ross; H. J. Price; J. S. Johnston (Plant Systematics and Evolution, 2004)

The cellular distribution and oxidation state of platinum(II) and platinum(IV) antitumour complexes in cancer cells - Matthew D. Hall; Carolyn T. Dillon; Mei Zhang; Philip Beale; Zhonghou Cai; Barry Lai; Anton P. J. Stampfl; Trevor W. Hambley (JBIC Journal of Biological Inorganic Chemistry, 2003)

Inferring long-term nutrient changes in southeastern Ontario lakes: comparing paleolimnological and mass-balance models - Euan D. Reavie; John P. Smol; Peter J. Dillon (Hydrobiologia, 2002)

Hard X-ray microprobe studies of chromium(VI)-treated V79 Chinese hamster lung cells: intracellular mapping of the biotransformation products of a chromium carcinogen - Carolyn T. Dillon; Peter A. Lay; Brendan J. Kennedy; Anton P. Stampfl; Zhonghou Cai; Peter Ilinski; William Rodrigues; Daniel G. Legnini; Barry Lai; Jörg Maser (JBIC Journal of Biological Inorganic Chemistry, 2002)

The use of ribosomal ITS to determine phylogenetic relationships within Sorghum - S. L. Dillon; P. K. Lawrence; R. J. Henry (Plant Systematics and Evolution, 2001)

Amplitude blanking related to the pore-filling of gas hydrate in sediments - Myung W. Lee; William P. Dillon (Marine Geophysical Research, 2001)

Sea-floor methane blow-out and global firestorm at the K–T boundary - M. D. Max; W. P. Dillon; C. Nishimura; B. G. Hurdle (Geo-Marine Letters, 1998)

Genetic structuring among Alaskan Pacific herring populations identified using microsatellite variation - M. O'Connell; M. C. Dillon; J. M. Wright; P. Bentzen; S. Merkouris; J. Seeb (Journal of Fish Biology, 1998)
Five highly variable microsatellite loci were used to investigate population structuring in Pacific herring Clupea pallasi collected from Kodiak Island, two sites in the Bering Sea and four sites within Prince William Sound, Alaska. All loci revealed high levels of variability with heterozygosity estimates ranging from 86 to 97% (mean heterozygosity: 89%). The variation was structured significantly among sites suggesting that the samples investigated were genetically distinct from each other. Genetic divergence was greatest between populations from the Bering Sea and those from Prince William Sound. The Kodiak Island and Point Chalmers samples appeared to be distinct from the Prince William Sound and Bering Sea populations. The observed genetic distance relationships among samples could be explained largely in terms of geographical separation.

Hypolimnetic alkalinity generation in two dilute, oligotrophic lakes in Ontario, Canada - P. J. Dillon; H. E. Evans; R. Girard (Water, Air, & Soil Pollution, 1997)